2012
DOI: 10.1140/epjb/e2012-21055-x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic conductance via atomic wires: a phase field matching theory approach

Abstract: A model is presented for the quantum transport of electrons, across finite atomic wire nanojunctions between electric leads, at zero bias limit. In order to derive the appropriate transmission and reflection spectra, familiar in the Landauer-Büttiker formalism, we develop the algebraic phase field matching theory (PFMT). In particular, we apply our model calculations to determine the electronic conductance for freely suspended monatomic linear sodium wires (MLNaW) between leads of the same element, and for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…7,25 After the formation of the SAC, small fluctuations (%15%) in the conductance were experimentally observed during elongation. 7 Several theoretical studies 21,28,29 demonstrated that these fluctuations occur when a single gold atom transitions from the 2D part of the nanowire to the SAC. This movement increases the number of atoms in the SAC by one and changes its state from even to odd and vice versa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,25 After the formation of the SAC, small fluctuations (%15%) in the conductance were experimentally observed during elongation. 7 Several theoretical studies 21,28,29 demonstrated that these fluctuations occur when a single gold atom transitions from the 2D part of the nanowire to the SAC. This movement increases the number of atoms in the SAC by one and changes its state from even to odd and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…This movement increases the number of atoms in the SAC by one and changes its state from even to odd and vice versa. It was found 28 that these states have different transmission spectra that make the conductance higher for odd numbers of atoms in the SAC and lower for even numbers. Another effect that has been satisfactorily explained is the gradual decrease of conductivity within a "plateau" during elastic elongation, which has been attributed to bond stretching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work we investigate the electronic scattering processes on the basis of the phase field matching theory (PFMT) [53], [54], originally developed for the scattering of phonons and magnons in nanostructures [55], [56], [57], [58], [59]. Our theoretical method is based on the appropriate phase matching of the Bloch states of ideal leads to the local states in the scattering region.…”
Section: Introductionmentioning
confidence: 99%
“…Our theoretical method is based on the appropriate phase matching of the Bloch states of ideal leads to the local states in the scattering region. In this approach the electronic properties of the system are described in the framework of the tight-binding formalism (TB) which is widely exploited for electronic transport calculations [54], [60], [61], [62], [63], and for simulating the STM images of nanostructures [64], [65]. In particular, we employ the appropriate Slater-Koster [66] type Hamiltonian parameters calculated on the basis of the Harrison tight-binding theory (HTBT) [67].…”
Section: Introductionmentioning
confidence: 99%